(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Feng Shui posits that proximity to hospitals may introduce unfavorable energy into residential and commercial environments. Nevertheless, in practice, several food and beverage (F&B) establishments located near hospitals continue to thrive, suggesting that certain spatial factors may contribute to their sustained success. This study aims to evaluate the environmental quality and spatial comfort of F&B outlets situated near three major hospitals in Tasikmalaya. Employing a qualitative case study methodology, the research integrates on-site observations with photographic documentation. Each establishment was analyzed through the lens of five geomantic principles Long, Sha, Xue, Shui, and Xiang as well as three spatial comfort dimensions: physical, visual, and haptic. The findings reveal that three long-standing establishments along Rumah Sakit Street demonstrate strong alignment with the Long, Xue, Shui, and Xiang factors, in addition to exhibiting a high degree of spatial comfort. Conversely, establishments on Otto Iskandardinata Street perform poorly across most geomantic and spatial parameters, except for haptic qualities, primarily due to suboptimal environmental configurations. On HZ Mustofa Street, two well-established outlets benefit from favorable Long, Xue, Shui elements and overall spatial comfort. These results underscore that the viability of sites near hospitals is contingent upon the nuanced interplay between Feng Shui principles and spatial comfort conditions, necessitating a context-specific approach to spatial assessment.